Strength properties of road base materials blended with waste limestones - Dychangco, Lydia Francisca T. (Animo Repository, 2012)
Road construction is one of the mostly developed infrastructures in the Philippines considering that it is the common inland transport in the country. Important factors that give quality to the road’s performance are the underlying soil layers of the road known as the subgrade, subbase and base. These soil layers play vital roles in the structural stability of the roads. However, it was noticed that there are constraints in the availability of the suitable materials making the construction costly. Most of the materials found in the site are substandard. This problem paved the opportunity to find potential use of waste limestones as blend to the conventional road base materials. The geotechnical properties of conventional road base materials blended with limestone at different proportions have been established, including specific gravities, particle size analyses, Atterberg limits, index densities, compaction characteristics, California bearing ratio (CBR) and unconfined compressive strength (UCS). In addition, Scanning Electon Microsocopy (SEM) photomicrographs were generated illustrating the micro fabric of the materials. Moreover, X-ray Diffraction (XRD) Analyses were obtained indicating the presence of minerals in the materials. The additional iv characterizations made from the SEM and XRD analyses helped in thoroughly examining the strength behavior of the controlled and blended mixtures. As a result, analysis showed correlations of limestone content to the index properties and strength characteristics of the materials. The results confirmed that the optimum strength can be produced at 50% blend of limestone which increased the unsoaked CBR, soaked CBR and UCS values up to 30%, 100% and 40%, respectively.